Radiobiological Aspects of FLASH Radiotherapy - Eline Hageman; Pei-Pei Che; Max Dahele; Ben J. Slotman; Peter Sminia (Biomolecules, 2022)
Radiotherapy (RT) is one of the primary treatment modalities for cancer patients. The clinical use of RT requires a balance to be struck between tumor effect and the risk of toxicity. Sparing normal tissue is the cornerstone of reducing toxicity. Advances in physical targeting and dose-shaping technology have helped to achieve this. FLASH RT is a promising, novel treatment technique that seeks to exploit a potential normal tissue-sparing effect of ultra-high dose rate irradiation. A significant body of in vitro and in vivo data has highlighted a decrease in acute and late radiation toxicities, while preserving the radiation effect in tumor cells. The underlying biological mechanisms of FLASH RT, however, remain unclear. Three main mechanisms have been hypothesized to account for this differential FLASH RT effect between the tumor and healthy tissue: the oxygen depletion, the DNA damage, and the immune-mediated hypothesis. These hypotheses and molecular mechanisms have been evaluated both in vitro and in vivo. Furthermore, the effect of ultra-high dose rate radiation with extremely short delivery times on the dynamic tumor microenvironment involving circulating blood cells and immune cells in humans is essentially unknown. Therefore, while there is great interest in FLASH RT as a means of targeting tumors with the promise of an increased therapeutic ratio, evidence of a generalized FLASH effect in humans and data to show that FLASH in humans is safe and at least effective against tumors as standard photon RT is currently lacking. FLASH RT needs further preclinical investigation and well-designed in-human studies before it can be introduced into clinical practice.